Synthesis of Novel VO(II)-Perimidine Complexes: Spectral, Computational, and Antitumor Studies - Gamil A. Al-Hazmi; Khlood S. Abou-Melha; Nashwa M. El-Metwaly; Kamel A. Saleh (Bioinorganic Chemistry and Applications)
A series of perimidine derivatives (L1–5) were prepared and characterized by IR, 1H·NMR, mass spectroscopy, UV-Vis, XRD, thermal, and SEM analysis. Five VO(II) complexes were synthesized and investigated by most previous tools besides the theoretical usage. A neutral tetradentate mode of bonding is the general approach for all binding ligands towards bi-vanadyl atoms. A square-pyramidal is the configuration proposed for all complexes. XRD analysis introduces the nanocrystalline nature of the ligand while the amorphous appearance of its metal ion complexes. The rocky shape is the observable surface morphology from SEM images. Thermal analysis verifies the presence of water of crystallization with all coordination spheres. The optimization process was accomplished using the Gaussian 09 software by different methods. The most stable configurations were extracted and displayed. Essential parameters were computed based on frontier energy gaps with all compounds. QSAR parameters were also obtained to give another side of view about the biological approach with the priority of the L3 ligand. Applying AutoDockTools 4.2 program over all perimidine derivatives introduces efficiency against 4c3p protein of breast cancer. Antitumor activity was screened for all compounds by a comparative view over breast, colon, and liver carcinoma cell lines. IC50 values represent promising efficiency of the L4-VO(II) complex against breast, colon, and liver carcinoma cell lines. The binding efficiency of ligands towards CT-DNA was tested. Binding constant (Kb) values are in agreement with the electron-drawing character of the p-substituent which offers high Kb values. Also, variable Hammett’s relations were drawn.